Lexical Interference of Angkola Mandailing Language on Indonesian Speech Among the Community of Tano Bato Village, Padang Sidempuan City: A Sociolinguistic Study - Rahmah Nasution, Atikah; Siregar, Lis Yulianti Syafrida (Jurnal Hata Poda, 2025)
This study aims to describe the form of lexical interference based on word classes in the Angkola Mandailing language towards Indonesian speech among the people of Tano Bato Village, Padang Sidempuan City, and the factors causing lexical interference of the Angkola Mandailing language towards Indonesian speech among the people of Tano Bato Village, Padang Sidempuan City. This type of research is a qualitative descriptive study. The method used in collecting data for this study is listening, free conversation, recording and note-taking techniques. The data analysis method in this study begins with describing all forms of conversation that the author found in the lexical interference of the Angkola Mandailing language in Indonesian speech among the people of Tano Bato Village, Padang Sidempuan City in the process that occurred. The next step is grouping all data according to the criteria for the form of lexical interference, and finally the data reduction of the results of this study is as follows: it was found that there was lexical interference of the Angkola Mandailing language on Indonesian speech among the people of Tano Bato Village, Padang Sidempuan City in the form of noun classes (nouns) consisting of 24 data, verb classes (verbs) consisting of 30 data, adjective classes (adjectives) consisting of 26 data, numeral classes (numeralia) consisting of 7 data, adverb classes (adverbs) consisting of 7 data and pronoun classes (pronouns) consisting of 6 data. The factors causing lexical interference of the Angkola Mandailing language with Indonesian speech among the Tano Bato Village community in Padang Sidempuan City include the bilingualism of the speech participants and the carrying over of habits in the mother tongue.